You've got 8 seconds : communication secrets for a distracted world - Hellman, Paul (AMACOM, 2017)
This book explains strategies and techniques for effective communication and presentations in a time of decreased attention spans. Whether pitching a project, giving a speech, selling a product, or writing emails, readers will learn how to design a strong message and say it in second; make routine information come alive; and convey confidence and command attention.